Bahasa Inggris - Garry Aditya Pranata; Nur Farhanah; Rudy Santoso; Budi Setiawan; Nurvita Nindita; Rahmad Rizal Budi Wicaksono (RSUP Dr. Kariadi, 2025)
Background: Indonesia is an endemic country for dengue virus infections, particularly in several regions. Dengue virus infection is a disease caused by the dengue virus and transmitted through the bite of the Aedes aegypti mosquito. In pregnancy, dengue virus infection increases the risk of dengue shock syndrome, pre-eclampsia, fetal distress, preterm delivery, cesarean section and maternal death. Despite the abundance of reports on dengue infection in pregnancy, data from Indonesia remain limited, particularly regarding clinical presentation, management decisions, and outcomes in resource-limited settings. This case series aims to contribute practical insights into clinical management, decision-making during the critical phase, and maternal-fetal outcomes in dengue-infected pregnancies. Cases: We report three cases of dengue virus infection during pregnancies. All three patients presented with acute fever and thrombocytopenia. Two of the three exhibited elevated in transaminase enzymes. One patient tested positive for NS1 antigen, while the other two tested positive for anti-dengue IgM and IgG. Blood component transfusions were administered to two patients during treatment. Two cases underwent termination of pregnancy via cesarean section due to indications of maternal and fetal distress. One neonate initially presented with an abnormal outcome but showed clinical improvement after intensive treatment. All three cases had normal maternal outcomes. Discussion: Pregnancy involves various physiological changes related to the cardiovascular, respiratory, and hematological systems. In these three cases, acute fever and thrombocytopenia (first and second cases) were observed, and there was no increase in hematocrit exceeding 20% of the baseline data, thus leading to a diagnosis of dengue fever. The WHO states that there is no difference in the amount and rate of intravenous fluid administration for pregnant and non-pregnant women, but recommends using pre-pregnancy body weight for fluid calculations. During the critical phase, termination of pregnancy should be performed only if the mother's life is threatened or if the patient experiences spontaneous labor. Timely multidisciplinary decision-making is crucial to optimize maternal and fetal outcomes, as fetal complications such as distress or preterm delivery may occur. In the first case, termination of pregnancy by cesarean section during the critical phase was performed due to induction failure and fetal distress. The neonate initially suffered moderate asphyxia but experienced clinical improvement after intensive care. Conclusion: Dengue virus infection in pregnancy increases the risk of morbidity and mortality for both mother and fetus. Therefore, strict monitoring and evaluation are needed, as well as management involving a multidisciplinary team that considers aspects of maternal and fetal safety.